Ethno-STEM in Science Education: A Systematic Literature Review (2020–2025) on Trends, Classroom Challenges, and Teacher Capacity in a Multicultural Context - Effendi Effendi; Ida Sriyanti; Ketang Wiyono; Leni Marlina; Rosdiana Rosdiana (Jurnal Penelitian Pendidikan IPA, 2025)
The Ethno-STEM approach has been recognised as an innovative strategy for enhancing the relevance and meaningfulness of STEM learning by integrating local wisdom and culture. Despite its great potential, its implementation faces various contextual challenges. This study aims to map current trends and analyse challenges in the development and implementation of Ethno-STEM learning models globally, with a specific focus on the Indonesian context for the period 2020-2025. The method used is a systematic literature review of empirical and conceptual articles from indexed databases. The results of the study identify three main trends: (1) the systematic integration of traditional knowledge with modern STEM frameworks, (2) synergy with Project-Based Learning (PjBL) models, and (3) the use of digital technology as a catalyst. The findings also reveal a number of critical challenges, particularly at the level of teacher readiness, such as a deficit of epistemic competence in transforming local wisdom into STEM curricula, as well as limitations in contextual teaching materials, time, and supporting infrastructure. Based on this synthesis, this study recommends multi-level strategies to overcome these obstacles, namely strengthening teacher capacity through continuous professional development programmes focused on cultural mapping, developing open access resource repositories, and advocating for affirmative policies to support budget allocation and tripartite collaboration (school-government-community). Thus, this study provides an evidence-based roadmap for realising more inclusive, culturally responsive, and sustainable STEM education